Effects of Father-Neonate Skin-to-Skin Contact on Attachment: A Randomized Controlled Trial - Er-Mei Chen; Meei-Ling Gau; Chieh-Yu Liu; Tzu-Ying Lee (Nursing Research and Practice)
This study examines how skin-to-skin contact between father and newborn affects the attachment relationship. A randomized controlled trial was conducted at a regional teaching hospital and a maternity clinic in northern Taiwan. The study recruited 83 first-time fathers aged 20 years or older. By block randomization, participants were allocated to an experimental (n=41) or a control (n=42) group. With the exception of skin-to-skin contact (SSC), participants from each group received the same standard care. Both groups also received an Early Childcare for Fathers nursing pamphlet. During the first three days postpartum, the intervention group members were provided a daily SSC intervention with their respective infants. Each intervention session lasted at least 15 minutes in length. The outcome measure was the Father-Child Attachment Scale (FCAS). After adjusting for demographic data, the changes to the mean FCAS were found to be significantly higher in the intervention group than in the control group. We recommend that nurses and midwives use instructional leaflets and demonstrations during postpartum hospitalization, encouraging new fathers to take an active role in caring for their newborn in order to enhance father-neonate interactions and establish parental confidence. This trial is registered with clinical trial registration number NCT02886767.